Analisis Faktor yang Berhubungan dengan Tindakan Pencegahan Tuberkulosis di Rsud Bayung Lencir Kabupaten Musi Banyuasin - Trijaniarti, Eva; Gustina, Erma; Ekawati, Dianita; Wahyudi, Arie (Universitas Baiturrahim, 2024)
Tuberculosis (TB) is still a public health problem in the world even though efforts to control TB have been implemented in many countries since 1995. TB disease can be cured with regular and routine treatment according to the treatment program. This study aims to analyze factors related to preventive measures for tuberculosis in patients at Bayung Lencir Regional Hospital, Musi Banyuasin Regency. This research is an analytical research with a cross sectional approach. The research was carried out at Bayung Lencir Regional Hospital, Musi Banyuasin Regency from January to February 2024. The population in this study were all families of tuberculosis patients seeking treatment at Bayung Lencir Regional Hospital, Musi Banyuasin Regency and samples were taken using total sampling techniques. Data analysis is univariate and bivariate analysis. Based on bivariate analysis using the chi-square test, namely gender P-Value: 0.029 (OR= 2.667), education P-Value: 0.015 (OR= 3.611), knowledge P-Value: 0.018 (OR= 2.877), attitude P-Value : 0.021 (OR= 2.825), family support P-Value: 0.013 (OR= 3.062), contact history P-Value: 0.002 (OR= 3.977). It can be concluded that there is a relationship between gender, education, knowledge, attitudes, family support and contact history with tuberculosis prevention measures. It is hoped that all officers at Bayung Lencir Regional Hospital, Musi Banyuasin Regency, will undergo regular examinations and screen patient contact history, as well as create GRABB TB innovations in an effort to provide quality services in an effort to prevent the transmission of tuberculosis.